When friends recommend: online purchasing behavior of Russian and Dutch people when prompted by recommendations from Facebook friends. Issue 3 (2nd September 2019) - Broeder, Peter; van Hout, Alies
ABSTRACT: This study investigates the relationship between product recommendations in a Facebook advertisement and the behavioral intentions of consumers, and to what extend this relationship is influenced by cultural differences in the tendency to avoid uncertain situations. In an online experiment 142 Dutch and 92 Russian people (average age 24 years) were presented with two advertisements of a GoPro camera in a Facebook context. The product recommendations in the advertisements differed in tie strength, that is, the amount and type of recommendations by close Facebook friends (strong ties) and other Facebook friends (weak ties). The results showed that the Dutch group had higher purchase intentions than the Russian group. Both groups are more influenced by strong tie online friends, than by weak tie online friends. The tie strength effect was stronger for the Dutch group. Meanwhile, compared to the Dutch group, the Russian group had a higher level of uncertainty avoidance, and also reported that they valued less the recommendations of other people, than those from their online friends. In addition, they were more willing to give the GoPro camera as a present to their close Facebook friends, than to other Facebook friends.